How To Increase Employee Performance Through Rewards And Training - Febrisi Dwita; Usep Suhud; ady Kurnia (Economy Deposit Journal (E-DJ), 2022)
The purpose of this research is to find out how to improve employee performance through rewards and training. This is behind the phenomenon of problems faced by the Fast Express company, namely the results of employee performance for the 2019 to 2021 period have not yet reached the expected target. Of the many factors that can affect employee performance, there are 2 main factors that will be examined by researchers, namely training and rewards. The research was conducted at PT Si Cepat Express, the research period was from March-May 2022. The research population was PT Si Cepat Express employees, especially in the Operations team, for which the exact number could not be known. This study uses non-probability and purposive sampling techniques. The sample consisted of 100 respondents, but only 82 complete questionnaires were considered usable. The results showed that training and rewards had a significant and positive effect on employee performance. This proves that the implementation of training and awards by the company Sicepat Express can have an effect on improving the performance of its employees.